Buyer Behavior of Home Appliances with Special Reference to Microwave Products in Bangalore City - Sudarsana Reddy, G.; Rajarashmi, P.S (Indian Journal of Marketing, 2004)
Electronics industry was in its nascent stage of development till the 1970s. Today, it is one of the fastest growing industries in the country. It has experienced a fast transformation towards the end of the century, which lead to the complete revolution in the Indian electronic sector. Microwaves have yet to make their felt in a big way in the country. All human beings are consumers from morning to evening. Everybody has to consume something whether it is purchased himself or by others. All buyers are consumers but all consumers are not buyers. Then who are the buyers and how they behave while purchasing a particular product is very important for marketers. Within the broad framework of marketing, buyer behavior is the most Interesting area and one is concerned with understanding why an individual buyer acts in certain buying related ways. All buyers are having differentia tastes, likes, and dislikes and adopt different behavior pattern while making buying decisions. Adam Smith stated that consumption is the sole end and purpose of all production Buying behavior may be defined as behavior exhibited by people in planning, purchasing and using economic goods and services. It is an Integral part of human behavior. Walter says buyer behavior is the process whereby individuals decide, what, when, where, how, and from whom to purchase goods and services.